Determination of contract base payments to feeder-pig finishers - J L Parcell; Michael R Langemeier (Kansas Agricultural Experiment Station Research Reports, 1996)
Risks associated with independent feeder-pig finishing have prompted finishers to seek alternative finishing and marketing methods. A means of reducing risk has developed through contract feeder-pig finishing. Research results indicated that slightly risk-averse finishers required contract base payments ranging from 11.00 to 30.00 per head. Strongly risk-averse finishers required contract base payments ranging from 8.50 to 19.00 per head. The lower end of the ranges is for a low-profit finisher. The upper end of the ranges is for a high-profit finisher.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Risk management; Contract feeder-pig finishing